Disability and sexuality: Desires and pleasures. (March 2018) - Loeser, Cassandra; Pini, Barbara; Crowley, Vicki
There is an ongoing missing discourse of pleasure in studies of sexuality and disability, and considerations of sexual pleasures and sexual desire in the lives of people with disabilities play very little part in public discourse. This opening article analyzes some of the major theoretical influences and debates informing prevailing assumptions about disability and sexuality. An exposition of the theoretical and conceptual terrains that underpin and shape this special issue works to canvas a series of often disparate sites of contestation, and suggests that disabled and sexual embodied subjectivities are much more than 'asexual' or 'hypersexual' pathological constructions. The articles explore the ways in which the intersection of disability and sexuality involves an understanding of the interlocking discourses of normality, sexuality, able-bodiedness, heteronormativity and desire, which can shape possibilities for sex, sexuality, pleasure and intimacy for people with a disability. What will become evident is that a greater attention to the phenomenology of sexual embodiment, pleasure, desire, and the diverse meanings of intimacy and the erotic, can make significant contributions to social and scholarly analyses of disability and sexuality. The utilization of different methodological approaches that can attend to complexity and diversity in the experience of sex and sexuality further constitutes part of the critique of ableist narratives of the 'normal' desiring and desirable subject that cannot account for the intersubjective conditions in which embodied subjectivity is constructed and pleasure experienced.